Current Approaches to the Preclinical Assessment of Endocrine Toxicity - D. A. Babkov (Безопасность и риск фармакотерапии, 2023)
Scientific relevance. Endocrine disruptors affect the functioning of endocrine organs, which leads to adverse drug reactions. Endocrine toxicity requires special attention in preclinical studies of candidate medicinal products.Aim. The study aimed to review international guidelines and approaches to assessing the risk of endocrine toxicity associated with medicinal products.Discussion. This review covers documents that provide a methodological framework for identifying and classifying a chemical compound as an endocrine disruptor. These documents include the following: Revised Guidance Document 150 on Standardised Test Guidelines for Evaluating Chemicals for Endocrine Disruption (Organisation for Economic Cooperation and Development, 2018), Nonclinical Evaluation of Endocrine-Related Drug Toxicity (Food and Drug Administration, 2015), and Guidance for the Identification of Endocrine Disruptors in the Context of Regulations (EU) No. 528/2012 and (EC) No. 1107/2009. The proposed algorithm for endocrine toxicity assessment involves collecting all available data on the test compound, such as the literature and previously obtained experimental data, including acute and subchronic toxicity data, and in silico predictions. Particular attention should be paid to the standard battery of preclinical chronic toxicity studies, which can identify most side effects associated with the endocrine system. The main endpoints for endocrine toxicity include changes in the mass and histopathology of the major endocrine organs (adrenal glands, testes, epididymides, ovaries, and the thyroid gland), oestrous cycle effects, reproductive toxicity, and transplacental action. A thorough assessment of the data obtained provides for the determination of unfavourable endocrine activity that requires further studies.Conclusions. The OECD guidelines offer a set of validated in vivo and in vitro tests that characterise the most important mechanisms of endocrine toxicity (oestrogen, androgen, thyroid, and steroidogenic endocrine pathways) by identified toxic effects. This approach allows researchers to identify potential endocrine disorders early in the drug development process and to optimise the scope of the required studies accordingly.